HUMAN RESOURCE PROVISION OF SOCIO-ECONOMIC SECURITY OF AN ENTERPRISE (Development Service Industry Management, 2025)
The article discusses the important role of human resource provision in the system of economic security of an enterprise, emphasizing its significance in protecting the business from various threats and risks that can impact the stability and development of the organization. As enterprises operate in constantly changing market, social, political, and economic conditions, ensuring economic security becomes an essential component for protecting the interests of the enterprise from both external and internal risks. Human resource provision, as a part of the economic security system, includes all aspects related to personnel management and has a significant impact on the overall effectiveness of the security management system.The article analyzes in detail the main components of the enterprise’s economic security system, particularly highlighting the interaction between human resource provision and other elements that form a comprehensive security management system. This interaction is crucial for ensuring the protection of the enterprise from potential threats, both from competitors and internal issues, such as conflicts, non-compliance with safety standards, fraud, and others. Special attention is given to the personnel policy, which is a strategic direction of human resource management. Personnel policy defines the main principles and approaches to working with personnel, as well as the factors that influence its formation, including labor market changes, social trends, and new technologies.The article also describes a model of human resource provision, which includes key components such as goals, tasks, functions, and principles of personnel management to ensure the economic security of the enterprise. Specifically, the key functions of human resource provision are identified, including: assessing personnel risks, forming a personnel strategy, employee monitoring, safety training, staff motivation, conflict resolution, managing confidential information, and monitoring employees’ psychological state. Each of these functions helps reduce the likelihood of negative impacts related to the human factor, which is an important element in the overall system of economic security of the enterprise.It is emphasized that effective human resource provision contributes to reducing risks associated with the human factor, such as inefficiency, dishonesty of employees, or psychological stress, which could lead to mistakes in the enterprise’s operations. This is a crucial element for ensuring the stability and security of the organization in a competitive environment and rapidly changing economic conditions. The article also highlights the importance of the close connection between human resource provision and personnel policy to achieve the strategic goals of the enterprise, including maintaining its competitiveness and development in the modern business environment.The conclusions of the article focus on the fact that human resource provision is an integral part of the economic security system of the enterprise and plays a key role in ensuring its stability, protection from threats, and achieving strategic goals.
Keywords: security; economic security of an enterprise; economic security system; human resource provision; personnel policy